Probiotics for the prevention of allergy: A systematic review and meta-analysis of randomized controlled trials (2015)
Background: Allergic diseases are considered a health burden because of their high and constantly increasing prevalence, high direct and indirect costs, and undesirable effects on quality of life. Probiotics have been suggested as an intervention to prevent allergic diseases. Objective: We sought to synthesize the evidence supporting use of probiotics for the prevention of allergies and inform World Allergy Organization guidelines on probiotic use. Methods: We performed a systematic review of randomized trials assessing the effects of any probiotic administered to pregnant women, breast-feeding mothers, and/or infants. Results: Of 2403 articles published until December 2014 identified in Cochrane Central Register of Controlled Trials, MEDLINE, and Embase, 29 studies fulfilled a priori specified inclusion criteria for the analyses. Probiotics reduced the risk of eczema when used by women during the last trimester of pregnancy (relative risk [RR], 0.71; 95% CI, 0.60-0.84), when used by breast-feeding mothers (RR, 0.57; 95% CI, 0.47-0.69), or when given to infants (RR, 0.80; 95% CI, 0.68-0.94). Evidence did not support an effect on other allergies, nutrition status, or incidence of adverse effects. The certainty in the evidence according to the Grading of Recommendation Assessment Development and Evaluation approach is low or very low because of the risk of bias, inconsistency and imprecision of results, and indirectness of available research.